Accounting Education: Current State and Prospects of Domestic Higher Education - Olga I. Averina (National Research Mordova State University, 2017)
Introduction: the problem of reforming the higher economic education in the field of training accountants and auditors is currently very relevant. Of particular interest in this context is the study of the current state and prospects for the development of the accountant profession and the tasks that face a modern accounting education. The purpose of the article is to assess the current state of preparation of accounting staff and the rationale for proposals for the formation of an educational trajectory in the field of training accountants and auditors, based on the priority of long life education, instead of education for life. Materials and Methods: during the research, general and special methods of scientific knowledge such as analysis and synthesis, scientific abstraction, dialectical, systemic, structural-functional, comparative and statistical methods were used. Results: we examined the current trends in the development of accounting education around the world and analysed the main differences. With the help of a random survey of students and employers, positive and negative aspects of the training programmes were revealed. The concept of transition to the accounting education throughout life (lifelong learning) is substantiated. Discussion and Conclusions: the purpose of accountants’ education is to nurture highly qualified professionals. This goal determines the direction and form of the learning process. The authors of the article give recommendations for improving accounting education in coordination with state programmes and professional requirements.